Quantitative EEG Tomography of Early Childhood Malnutrition - Taboada-Crispi, Alberto; Bringas-Vega, Maria L.; Bosch-Bayard, Jorge; Galán-García, Lidice; Bryce, Cyralene; Rabinowitz, Arielle G.; Prichep, Leslie S.; Isenhart, Robert; Calzada-Reyes, Ana; VIrues-Alba, Trinidad; Guo, Yanbo; Galler, Janina R.; et al. (Frontiers in Neuroscience, 2018)
The goal of this study is to identify the quantitative electroencephalographic (qEEG) signature of early childhood malnutrition (PEM). To this end, archival digital EEG recordings of 108 participants in the Barbados Nutrition Study (BNS) were recovered and cleaned of artefacts (46 PEM children limited to the first year of life and 62 healthy controls). The participants of the still ongoing BNS were enrolled in 1973 and EEGs for both groups were recorded in 1977-78 at 5 to 11 years. Scalp and source EEG z spectra were obtained by comparison with the normative Cuban Human Brain Mapping database. Differences between both groups in the z spectra (for all electrode locations and frequencies) were assessed by t-tests with thresholds corrected for multiple comparisons by permutation tests. Four clusters of differences were found: a) increased theta activity (3.91 to 5.86 Hz) in electrodes T4, O2, Pz and in the sources of the supplementary motor area (SMA); b) decreased alpha1 (8.59 to 8.98 Hz) in fronto-central electrodes and sources of widespread bilateral prefrontal are; c) increased alpha2 (11.33 to 12.50 Hz) in temporo-parietal electrodes as well as in sources in centro-parietal areas of the right hemisphere; and d) increased beta (13.67 to 18.36 Hz), in T4, T5 and P4 electrodes and decreased in the sources of bilateral occipito-temporal areas. Multivariate Item Response Theory (MIRT) of EEGs scored by expert visual inspection revealed a neurophysiological latent variable which indicated excessive paroxysmal and focal abnormality activity in the PEM group. A robust biomarker construction procedure based on elastic-net regressions and 1000-cross-validations was used to: i) select stable variables and ii) calculate the area under ROC curves (AUC). Thus, qEEG differentiated between the two nutrition groups (PEM vs. control) as did visual inspection of the EEG scored by experts (AUC=0.83). Since PEM is a global public health problem with lifelong neurodevelopmental consequences, our finding of consistent differences between PEM and controls, both in qualitative and quantitative EEG analysis, suggest that this technology may be a source of scalable and affordable biomarkers for assessing the long-term brain impact of early PEM.